El contrato de concesión en la organización del transporte público de Bogotá (2011)
"The mobility in Bogota in great proportion corresponds to the public transport, which is constituted in one of the fundamental urban problems, in reason to the lack of planeación and public policies that go of the hand with the growth of the city. To grant solution to these losses citadinos there has been implanted a contractual model named ""Concession"" who redounds to mutual benefits both for the State and for the private sector, of conformity with the evolution of the public transport, one must come to the public biddings to award the contracts that contain the routes and areas of Bogota with analogous characteristics to those of the System Trasmilenio and hereby to improve the movement of the citizens as well as his quality of life and general well-being."